FINANCIAL MARKETS AND INVESTMENT RISKS FOR INDIVIDUAL SMALL INVESTORS: CHALLENGES AND STRATEGIES FOR RISK MITIGATION - Michael Chen (Ecomind Press, 2025)
The rise of retail investing in financial markets has empowered individual small investors, but it has also exposed them to significant risks. This paper explores the various risks that small investors face when participating in financial markets, including market volatility, liquidity risk, and information asymmetry. It further examines the strategies available to mitigate these risks, such as diversification, risk tolerance assessment, and the use of financial technology. The study highlights recent trends in retail investment, the role of behavioral finance, and the increasing reliance on digital platforms. Drawing on recent data and research (2023–2025), the paper concludes that while financial markets offer opportunities for wealth creation, small investors must adopt informed strategies to manage risks effectively and avoid substantial financial losses.